Perioperative Management of Patients with Rheumatic Diseases: Glucocorticoids, DMARDs, Biological Agents and NSAIDs - V. V. Lyalina; S. V. Borisovskaya; E. A. Skripnichenko; O. A. Ettinger; T. M. Padzheva; I. G. Nikitin (Архивъ внутренней медицины)
The rheumatic patients are characterized by various structural and functional changes, caused by chronic disease the necessity of constant medication intake, including anti-inflammatory drugs and immunosuppressants. In this regard, the rheumatic patients have an increased risk of intraoperative and postoperative complications. The purpose of this publication is to review current recommendations on the topic of perioperative management of rheumatic patients. The publication consists of two parts. In the first part we review the issues of perioperative administration of steroids, disease-modifying antirheumatic drugs, biologics and nonsteroidal anti-inflammatory drugs.